The Relationship Between the Laws of Conservation of Energy and Momentum for Low Speed Impact of Several Bodies - Chernyavsky, D. I.; Gapon, D. D. (Journal of Applied Nonlinear Dynamics, 2026)
The classical theory of stereo-mechanical impact is widely used in practice. This theory is based on the law of conservation of energy and the law of conservation of momentum. The main purpose of this study is to determine the optimal mass ratios and velocity ratios of colliding bodies, which are the basis of the impact mechanism. The solution of this problem is necessary for calculating the maximum energy efficiency of the impact system. In this paper, we obtain a coupling equation for the energy and momentum conservation laws, as well as for the Newtonian restitution coefficient equation for a simultaneous central stereo-mechanical impact of bodies.